Analisa Pengaruh pH Air dan Tinggi Muka Air di Lahan Rawa Terhadap Produktivitas Padi - Lilik Sriwahyuni; Widandi Soetopo; Moch. Sholichin (Jurnal Penelitian Pendidikan IPA, 2025)
The area of swamp land in Indonesia is spread across 5 (five) large islands, namely Sumatra, Java, Kalimantan, Sulawesi and Papua. The results of spatial analysis conducted by BBSDLP (2015) the area of ​​swamp land in Indonesia is 34.12 million ha (17.92% of the total land area of ​​Indonesia) consisting of tidal swamps of 8.92 million ha and lowland swamps of 25.21 million ha, spread across Sumatra 12.93 million ha, Kalimantan 10.02 million ha, Papua 9.87 million ha, Sulawesi 1.05 million ha, Maluku 0.16 million ha and Java 0.09 million ha. The aim of the research is to examine the formulation of the problem are analyzing the effect of water level and water pH on rice productivity at the research location. The F test shows that the variables of Water Level and Water pH together have a significant effect on rice productivity of 79.1%. The need for Operations and Maintenance Officers, the participation of both the Water Users Farmers Association (P3A) and the community as farmers to regulate the water level in rice fields so that it is in optimum condition so that it can increase rice productivity